Financial Feasibility and Financial Performance Analysis of the LALABO (Laundry Laboratory) Business Plan as a Hypoallergenic Laundry Service Business Model - Giovany, Kenny; Indradewa, Rhian; Abadi, Ferryal; Ramadhan, Yanuar (Syntax Literate, 2026)
With the fast-paced urban lifestyle, there is a growing demand for convenient and technology-driven laundry care services. LALABO (Laundry Laboratory) is a laundry service that offers an integrated system supported by a digital platform and unique features such as express service and specialized baby laundry. The purpose of this research is to investigate the financial viability and performance of the LALABO business plan. The research employs a descriptive quantitative approach using a business feasibility study. Data were obtained through five-year financial projections, analyzed using cash flow statements, balance sheets, income statements, investment feasibility analyses, and financial ratio assessments as secondary data. Findings from the study indicate that LALABO incurred a loss in its first year of operation but achieved profitability with notable improvement in subsequent years. The Net Present Value (NPV) of IDR 10.38 billion and the Internal Rate of Return (IRR) of 37.42%, which exceeds the Weighted Average Cost of Capital (WACC) of 12.07%, demonstrate that the business is financially feasible. Furthermore, the results of the financial ratio analysis show increasing levels of profitability, solvency, and liquidity. Consequently, LALABO has strong potential to become a viable technology-based laundry service business model. The study suggests that integrating hypoallergenic service differentiation with digital operational systems enhances both market competitiveness and long-term financial sustainability, providing an innovative model for the laundry service industry.